2013
DOI: 10.1111/j.1728-4465.2013.00341.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender Attitudes and Fertility Aspirations among Young Men in Five High Fertility East African Countries

Abstract: The relationship between women's attitudes toward gender equality and their fertility aspirations has been researched extensively, but few studies have explored the same associations among men. Using recent Demographic and Health Survey data from five high fertility East African countries, we examine the association between young men's gender attitudes and their ideal family size. Whereas several DHS gender attitude responses were associated with fertility aspirations in select countries, men's greater toleran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…Both views of masculinity can affect family planning use by women and men [36, 37]. Where men and boys have been exposed to gender equality programming, they are more likely to report increased contraceptive use, including condom use.…”
Section: Resultsmentioning
confidence: 99%
“…Both views of masculinity can affect family planning use by women and men [36, 37]. Where men and boys have been exposed to gender equality programming, they are more likely to report increased contraceptive use, including condom use.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in Kenya, the national prevalence of HIV infection is estimated at 5.6% with an estimated 260 000 HIV‐serodiscordant couples . HIV‐infected individuals have reproductive desires that cannot be ignored and they knowingly risk HIV transmission in order to conceive . In HIV‐serodiscordant partnerships in which pregnancy occurs, the risk of HIV acquisition nearly doubles for the uninfected partner compared with partnerships in which pregnancy does not occur .…”
Section: Introductionmentioning
confidence: 99%
“…4 HIV-infected individuals have reproductive desires that cannot be ignored and they knowingly risk HIV transmission in order to conceive. [5][6][7] In HIV-serodiscordant partnerships in which pregnancy occurs, the risk of HIV acquisition nearly doubles for the uninfected partner compared with partnerships in which pregnancy does not occur. 5 Furthermore, providing fertile HIV-infected women with the possibility of preserving their fertility and a safer option for conception is empowering given the stigma and isolation that they may already encounter as a result of their HIV status, particularly in cultures where reproduc-tion defines one's value in society.…”
Section: Introductionmentioning
confidence: 99%
“…Studies into gender attitudes and fertility aspirations among men in East African countries with high fertility found that women’s fertility preferences are strongly influenced by their husbands’ desire to have many children [27,28]. In West Pokot County, Kenya, men and women highlighted low male involvement in FP as the major obstacle to the uptake of FP services [17].…”
Section: Introductionmentioning
confidence: 99%